The city life of youths in Greenland - Rygaard, Jette (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2008)
AbstractIn traditional Greenlandic literature as among the critics of modern civilisation, modernisation and urbanisation correspond to alienation, loneliness, urban misery, and stress. On the other hand, more and more people try to get to the big cities. An urban centre like Nuuk seems to be a success. In contrast, the small remote settlements in Greenland continuously face major problems of social disorders and poverty because of extreme living costs and unemployment. In this article, life in the city is discussed through the eyes of youths from Nuuk and the rural East Greenlandic small town of Ittoqqortoormiit. The data come from three succeeding projects, CAM I-II-III, which included photos and texts from young Greenlanders between 10 and 20 years of age regarding themes such as “my school,” “my friends,” “my media,” and “my city.” An analysis of the material produced reveals that the views of these young people fit urban theories concerning life style and behaviour; rural dwellers submitting to a life with close connections and tranquillity opposite to the hectic city dwellers’ life in an urban area.